2021
DOI: 10.33503/ebio.v6i01.792
|View full text |Cite
|
Sign up to set email alerts
|

Fish diversity and heavy metal content mercury (Hg), arsenic (As) on the water and fish in Cikaniki river, Bogor regency

Abstract: Organisms that live in waters are sensitive to changes in the water quality in which they live. The quality of the water in the Cikaniki River is threatened by the gold mining industry, illegal mining, agricultural activities, and settlements. One of the organisms that will be affected by these environmental changes is fish. This research aims to obtain a diversity index of fish species and to determine the content of heavy metals Mercury (Hg), Arsenic (As) on the water, and fish. Research on the diversity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It has been reported that heavy metals in the environment will be enriched in fish, and there is a response relationship between the abundance of fish species and heavy metals in the environment, which affects the composition and abundance of organisms to varying degrees [ 37 ]. Redundancy analysis is a ranking method combining regression analysis with principal component analysis, which can intuitively reflect the response of species variables to environmental variables [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that heavy metals in the environment will be enriched in fish, and there is a response relationship between the abundance of fish species and heavy metals in the environment, which affects the composition and abundance of organisms to varying degrees [ 37 ]. Redundancy analysis is a ranking method combining regression analysis with principal component analysis, which can intuitively reflect the response of species variables to environmental variables [ 38 ].…”
Section: Resultsmentioning
confidence: 99%